PENERAPAN MODEL PROBLEM BASSED LEARNING (PBL) DALAM PEMBELAJARAN MENGANALISIS TEKS BIOGRAFI PADA PESERTA DIDIK KELAS X SMK NEGERI 1 KAPETAKAN KABUPATEN CIREBON TAHUN AJARAN 2022/2023 - Mulyani, Weni Sri; Hasanudin, Ade; Apriyanto, Ade (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study is motivated by the students' low ability to analyze biography texts and their lack of motivation, which leads to their reluctance to complete learning tasks. One effective learning model that can be used is the problem-based learning (PBL) model for analyzing biography texts. The objectives of this study are: 1) to determine the effectiveness of the PBL model in teaching biography texts to class X students at SMKN 1 Kapetakan in the 2022/2023 academic year, and 2) to describe the learning activities of biographical texts using the PBL model in class X at SMKN 1 Kapetakan in the 2022/2023 academic year. This research follows an experimental method with a quasi-experimental design called the nonequivalent control group design. The data analysis shows that the learning process of analyzing biography texts in class X at SMKN 1 Kapetakan in the 2022/2023 academic year has improved after using the problem-based learning model. This is supported by the results of the initial and final tests, which were analyzed using the independent sample t-test. The t-count value is 0.3887, while the t-table value is 0.2024. Therefore, t-count (0.3887) > t-table (0.2024). Furthermore, the observation results indicate that the problem-based learning model enhances student engagement in the learning process of analyzing biography texts for class X students at SMKN 1 Kapetakan in the 2022/2023 academic year.